Impact of the Cancer and Aging Research Group (CARG) chemotherapy toxicity (tox) risk score on the benefit of a geriatric assessment–driven intervention (GAIN) among older adults with cancer. Issue 28 (1st October 2022) - Crook, Christiana; Sun, Can-Lan; Kim, Heeyoung; Soto Pérez de Celis, Enrique; Chung, Vincent; Koczywas, Marianna; Fakih, Marwan; Chao, Joseph; Cabrera Chien, Leana; Charles, Kemeberly; Katheria, Vani; Trent, Monica; et al.
Abstract : 235 Background: The CARG tox score can predict risk of chemotherapy-related tox in older adults with cancer. GAIN can reduce tox vs standard of care (SOC) among these patients (pts); GAIN's impact across CARG risk groups is unknown. Methods: A secondary analysis of the GAIN randomized clinical trial (NCT02517034) of pts aged ≥65 (solid tumor diagnosis, starting a new chemotherapy) was performed. Pts were randomized 2:1 to receive GAIN vs SOC and were categorized into low (0-5), medium (6-9), and high (10-20) risk groups according to CARG score. The primary outcome was incidence of grade 3-5 tox. Chi-square/Fisher's exact tests were used to compare outcomes (GAIN vs SOC, stratified by risk groups). Log-rank tests were used to compare 1-year survival across risk groups. Results: This analysis included 600 pts: 26.5% low risk, 45.2% medium risk, 28.3% high risk. Table shows pt/treatment characteristics. For pts with low/medium risk scores, GAIN demonstrated a 14.0% (95% CI 4.1%-23.9%) reduction in tox vs SOC (p = 0.006). No significant reduction in tox was observed among pts with high risk scores (p = 0.86). One-year survival (GAIN vs SOC) for each risk group was 73.6% vs 67.4% (low risk), 68.5% vs 64.5% (medium risk), and 57.3% vs 61.7% (high risk), respectively (log-rank p = 0.10). Conclusions: Older adults with low/medium, but not high, CARG risk scores benefit from GAIN. Additional strategies may be needed to improve outcomes for pts with high CARG risk scores. Clinical trial information: NCT02517034. Patient/treatment characteristics (N = 600). Low risk, GAIN (n = 110) Low risk, SOC (n = 49) Medium risk, GAIN (n = 178) Medium risk, SOC (n = 93) High risk, GAIN (n = 110) High risk, SOC (n = 60) Age, median (range) 68 (65-87) 70 (65-88) 70 (65-88) 71 (65-87) 71 (65-91) 74 (65-87) Primary genitourinary cancer, n (%) 9 (8.18) 2 (4.08) 28 (15.73) 13 (13.98) 26 (23.64) 12 (20.00) Primary breast cancer, n (%) 48 (43.64) 19 (38.78) 31 (17.42) 20 (21.51) 13 (11.82) 4 (6.67) Primary gynecologic cancer, n (%) 18 (16.36) 9 (18.37) 12 (6.74) 7 (7.53) 5 (4.55) 3 (5.00) Primary gastrointestinal cancer, n (%) 9 (8.18) 6 (12.24) 68 (38.20) 30 (32.26) 57 (51.82) 31 (51.67) Primary lung cancer, n (%) 19 (17.27) 11 (22.45) 34 (19.10) 17 (18.28) 6 (5.45) 8 (13.33) Other primary cancer, n (%) 7 (6.36) 2 (4.08) 5 (2.81) 6 (6.45) 3 (2.73) 2 (3.33) Initial dose reduction, n (%) 42 (38.2) 18 (36.7) 58 (32.6) 40 (43.0) 47 (42.7) 28 (46.7) Received poly-chemotherapy, n (%) 54 (49.1) 22 (44.9) 129 (72.5) 68 (73.1) 86 (78.2) 47 (78.3)